Si no es con las mandas y limosnas que buenos christianos nos hicieren…”. The importance of almsgiving in financing the ransom of captives (16th and 17th centuries) - Marcos Martín, Alberto (Cuadernos de Historia Moderna, 2025)
The long conflict between the Spanish Monarchy and the Ottoman Empire and its allies, the Muslim countries of North Africa, created a problem of considerable dimensions in the form of a spectacular increase in the number of captives, slaves and renegades. This gave rise to a trade in men often linked to the trade in goods, and generated a “ransom economy” whose contours are known to us but not its depth. This article analyses some of the particularities of this trade and this economy, and emphasises the role played by charitable piety in financing the ransoms of Christian captives during the 16th and 17th centuries.